2011
DOI: 10.1016/j.bbi.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic mental stress and atherogenic diet on the immune inflammatory environment in mouse aorta

Abstract: Inflammation and stress are regarded as two important atherogenic factors. Because stress can affect leukocyte distribution, we hypothesized that stress-mediated leukocyte extravasation can modify the inflammatory environment of the arterial wall possibly contributing to atherogenesis. To test this hypothesis we evaluated the inflammatory environment of the aorta in C57Bl/6 mice subjected to 3 and to 12 months of chronic stress and compared it to age matched non-stressed animals. Experiments were carried out i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…66 In contrast, it was recently reported that up to 12 months of exposure to chronic stress in C57Bl/6J mice fed an atherogenic diet suppressed the development of intimal foam cells and attenuated the atherogenic histological changes in the aorta. 67 Although the cited studies have shown that the effect of stress on atherosclerosis is related to the particular type of stressor, the present finding that acute stress actually accelerates RCT was unanticipated. If we consider that a shortterm stress period enables the body with adaptive responses to protect against a threat/risk of injury, then increased synthesis of glucocorticoids may represent one of the body's auto pharmacological protective mechanisms in various disease processes.…”
Section: Discussionmentioning
confidence: 46%
“…66 In contrast, it was recently reported that up to 12 months of exposure to chronic stress in C57Bl/6J mice fed an atherogenic diet suppressed the development of intimal foam cells and attenuated the atherogenic histological changes in the aorta. 67 Although the cited studies have shown that the effect of stress on atherosclerosis is related to the particular type of stressor, the present finding that acute stress actually accelerates RCT was unanticipated. If we consider that a shortterm stress period enables the body with adaptive responses to protect against a threat/risk of injury, then increased synthesis of glucocorticoids may represent one of the body's auto pharmacological protective mechanisms in various disease processes.…”
Section: Discussionmentioning
confidence: 46%
“…13 Interestingly, VCAM-1 is a key vascular inflammatory marker that increases under more severe stress protocols in ApoE À/À or C57BL/6 mice. 36,37 The studies also suggest that stress and an atherogenic diet increase vascular inflammation but have different effects on atherogenesis. In the current study, we confirmed elevated expression of VCAM-1 in carotids from SJL inbred mice or recipient SJL chimeras.…”
Section: Discussionmentioning
confidence: 99%
“…At 10 weeks WD, a mental stress protocol adapted from Marcondes et al [18], was initiated and consisted of 3 different triggers: water avoidance, damp bedding and restraint stress. To induce water avoidance stress, mice were placed in an empty cage filled with 0.3 cm of water.…”
Section: Mental Stress Protocolmentioning
confidence: 99%